Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Kelas I Di SD Alam Cordova Probolinggo - Dewi Mustokoweni (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This study aims to determine student learning outcomes by using the Discovery Learning learning model, as well as knowing the effectiveness of applying this model. This research was conducted at SD Alam Cordova Probolinggo with 4 research subjects, consisting of 3 male students and 1 female student. This study used the Classroom Action Research (CAR) method which was carried out in two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. Data collection is done through tests, observations, and documentation. Based on student learning outcomes in cycle I, it reached 75%, a number of 3 students scored below 70, and there was only one student or 25% of students who were in the complete category, namely those who received a KKM score of 70 with an average score of 57. II student learning outcomes reach 100% where all students in the class get the complete category and have obtained a KKM score of 70 with an average value of 77. It can be concluded that the Application of the Discovery Learning Learning Model can improve learning outcomes in learning Mathematics in class I SD Alam Cordova Probolinggo.